Estudos bioecológicos dos afídeos da alfafa - Cunha, Suzan Beatriz Zambon da (2013)
Aphids (Hemiptera: Aphidoidea) are insects considered as pests in many crops. Acyrthosiphon pisum, Aphis craccivora and Therioaphis trifolii f. maculata, occur often in alfalfa crops (Medicago sativa) in Brazil, causing direct and indirect damage to the plants. In this study designed to determine the seasonal fluctuation of aphids and their predators in alfalfa crop and its relationships with climatic variables by canonical correspondence analysis; to verify if there is in laboratory selectivity predators feeding, Cycloneda sanguinea, Harmonia axyrids and Hippodamia convergens for aphid A. pisum, A. craccivora and T. trifolli f. maculata to establish their predators in field culture, as well as to compare the various predators, as their efficiency in preying upon aphids using the serological technique. This technique is based on reactions such as antigen / antibody where the antibodies are obtained for the pest of interest and how antigens are used on many pest consumers. The gathering of aphids and their predators were conducted from August 2011 to July 2012 in experimental fields of alfalfa Crioula located at the Embrapa Unit, São Carlos SP. Acyrthosiphon pisum was the predominant aphid in the culture during the study period. Considering all the species, the highest population peak was observed in March/2012 and the lower in January/2012. According to canonical correspondence analysis, none of the environmental variables influenced significantly the seasonal fluctuation of aphids. Regarding the predators, 2.161 specimens were collected including insects and spiders. Among the insects the following families: Coccinellidae, Carabidae, Nabidae, Syrphidae, Dolichopodidae, Geocoridae, Reduviidae, Pentatomidae, Chrysopidae and Dermaptera. Among the spiders, Salticidae, Thomisidae; Lycosidae; Ctenidae; Nephilidae; Araneidae; xi Sparassidae; Theridiidae; Pholcidae; Trocantheriidae; Lymphidae and Sicariidae ocurred. The coccinellids were the most abundant insects and Harmonia axyridis was the most abundant species. It was also observed that the population of aphids and coccinellids follow the typical pattern of predator-prey relationship. The presence of natural enemies and the management of cutting the alfalfa influenced the dynamics of aphid populations. According to the results of the serological tests of all predators tested, 508 reacted with any of the antisera, resulting in 23,5% of positive results. Heterologous positive reactions were recorded with predators stored in a freezer at -2 °C for over a year showing that freezing does not affect the results of serological reactions. Syrphid and chrysopids were the predators with the highest percentage of positive serological reactions. The food preference tests in the laboratory showed that the coccinellids C. sanguinea, H. axyridis and H. convergens have a preference for A. craccivora when one compare to other species of aphids offered